PERHIMPUNAN PALANG MERAH INDONESIA (PMI) - Khairina Habib Rangkuti; Nuri Al Fitriyani; Nur Nani Siagian; Usiono Usiono (JOURNAL SAINS STUDENT RESEARCH, 2025)
The Indonesian Red Cross Society (Palang Merah Indonesia or PMI) is a humanitarian and social organization established on September 17, 1945. PMI plays a vital role in disaster management, healthcare services, and the promotion of humanitarian awareness. The organization has a well-structured system extending from national to local levels, focusing on community capacity building and fulfilling humanitarian needs. This research adopts a mixed- method approach, including observation, interviews, and literature studies, to explore PMI's background, structure, and role in aiding communities. Findings indicate that PMI continues to play a significant role in fostering solidarity, independence, and mutual cooperation through its programs and services.